Iron transformation behavior in coal ash slag in the entrained flow gasifier and the application for Yanzhou coal. (1st February 2019) - He, Chong; Bai, Jin; Li, Weicheng; Kong, Lingxue; Xu, Jiang; Guhl, Stefan; Li, Xiaoming; Bai, Zongqing; Li, Wen
Highlights: Iron transformations during tapping process are quantified for the first time. Iron content in the liquid phase decreases as spinel and melilite precipitate. The model for Fe transformation including Fe 2+ /Fe 3+ and Fe-minerals is built. The slag in Shell gasifier is more reduced than that in Texaco gasifier. The models built in this work benefits the utilization of iron rich coal. Abstract: Coal ash slag viscosity is the most important parameter for the design and the stable running of entrained flow gasifier. Iron serves as the most abundant variable-valence element in coal ash slag, but the effects of iron in coal ash slag on viscosity and slag crystallization under the gasification conditions are not available. In this research, the iron transformation behaviors are discussed, and predictive models for iron transformation based on the ash chemical composition, atmosphere, slag residence time and temperature are established. In the fully liquid slag, Fe 2+ /Fe 3+ increases with SiO2 /Al2 O3 (mass ratio) and temperature, but it decreases with the increasing iron content, α value (α = CaO/(SiO2 +Al2 O3 ), mass ratio), and oxygen partial pressure. The equilibrium and kinetic model considering CO and H2 diffusion is built for prediction of Fe 2+ /Fe 3+ in slag at given temperature, oxygen partial pressure, and residence time. The model is applied to predict the Fe 2+ /Fe 3+ of Yanzhou coal and it is found that Fe 2+ in Shell slag is higher than that in Texaco slag. In partial crystalline slag, the iron transformation is sensitive to the variations of SiO2 +Al2 O3 and SiO2 /Al2 O3 because of the formations of melilite and spinel. The prediction models for melilite and spinel transformation are also built, but the result has not been validated due to lack of in-situ results in the commercial gasifier. The above models offer the guidance for the prediction and adjustment of slag behavior in the gasifier, especially for the iron-rich coal.